Employee views of leveraged buy-out transactions - Lambert, M; Moreno, N; Phalippou, L; Scivoletto, A (2021)
A large sample of employee reviews shows a decline in satisfaction after a Leveraged Buy-Out (LBO), but with significant heterogeneity. The key driver is the previous ownership structure. For Private-to-Private transactions, dissatisfaction is concentrated in non-management employees and comes mostly from how management treats them. In Public-to-Private transactions, the dissatisfaction is stronger, multi-faceted, and present for all employees, including management. Industry and Private Equity sponsor fixed effects are significant, but second order. Other ownership changes (M&A, IPO) trigger less dissatisfaction.